Comfort and Convenience at Audley End House. Issue 1 (2013) - Palmer, Marilyn; West, Ian
<x content-type="archive" xml:space="preserve">Abstract</x> Increasing interest has been shown in the ways in which country-house owners in the 18th and 19th centuries adapted their houses to incorporate new technical innovations which would improve their comfort, something that has been explored by the authors in their Country House Technology Project. Audley End House was little modernized from the second half of the 19th century onwards and was also the first great house to be acquired by the Ministry of Works. As a consequence, many of the fixtures and fittings associated with early water supply, communications, lighting, heating and sanitation remain within the house, while their interpretation has been aided by the excellent survival of the Braybrooke family archives. This article explores the ways in which some of the owners of Audley End House were pioneers in technological innovation and illustrates what remains of their work within the house and its estate.